Chemostratigraphy of the Mina Verdún Group and other cement-grade Proterozoic limestone deposits in Uruguay - Gaucher, Claudio (2007)
The Mina Verdún Group (MVG) was erected by Poiré et al. (2003) to include a sedimentary succession exposed in the homonymous mine, which is made up (from base to top) of (Fig. 2): -Don Mario Formation: metapelites -La Toma Formation: marls -El Calabozo Formation: grey stromatolitic limestones -Gibraltar Formation: dolomitic marls, red limestones and massive dolostones Thickness of the succession at its stratotype reaches 285 m. An important feature of the thick (up to 170 m) limestones of El Calabozo Formation is the occurrence of a stromatolite assemblage composed almost exclusively by Conophyton (Fig. 2). These limestones are of considerable economic importance, because they constitute the basis of a large cement industry. A minimum age for the succession is provided by the unconformably overlying Las Ventanas Formation, which on the basis of acritarch biostratigraphy is assigned to the lower Ediacaran (635-575 Ma, Blanco & Gaucher, 2005). Gaucher et al. (2004d) assign the succession exposed in the Burgue o limestone Quarry, 40 km to the south of Mina Verdún, to the MVG. The succession exposed in the quarry, 150 m in thickness, includes (from base to top): metamarls, limestones, stromatolitic Conophytonlimestones and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. Mina Verdún, to the MVG. The succession exposed in the quarry, 150 m in thickness, includes (from base to top): metamarls, limestones, stromatolitic Conophytonlimestones and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. considerable economic importance, because they constitute the basis of a large cement industry. A minimum age for the succession is provided by the unconformably overlying Las Ventanas Formation, which on the basis of acritarch biostratigraphy is assigned to the lower Ediacaran (635-575 Ma, Blanco & Gaucher, 2005). Gaucher et al. (2004d) assign the succession exposed in the Burgue o limestone Quarry, 40 km to the south of Mina Verdún, to the MVG. The succession exposed in the quarry, 150 m in thickness, includes (from base to top): metamarls, limestones, stromatolitic Conophytonlimestones and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. Mina Verdún, to the MVG. The succession exposed in the quarry, 150 m in thickness, includes (from base to top): metamarls, limestones, stromatolitic Conophytonlimestones and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. Conophyton (Fig. 2). These limestones are of considerable economic importance, because they constitute the basis of a large cement industry. A minimum age for the succession is provided by the unconformably overlying Las Ventanas Formation, which on the basis of acritarch biostratigraphy is assigned to the lower Ediacaran (635-575 Ma, Blanco & Gaucher, 2005). Gaucher et al. (2004d) assign the succession exposed in the Burgue o limestone Quarry, 40 km to the south of Mina Verdún, to the MVG. The succession exposed in the quarry, 150 m in thickness, includes (from base to top): metamarls, limestones, stromatolitic Conophytonlimestones and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. Mina Verdún, to the MVG. The succession exposed in the quarry, 150 m in thickness, includes (from base to top): metamarls, limestones, stromatolitic Conophytonlimestones and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. o limestone Quarry, 40 km to the south of Mina Verdún, to the MVG. The succession exposed in the quarry, 150 m in thickness, includes (from base to top): metamarls, limestones, stromatolitic Conophytonlimestones and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. Conophytonlimestones and massive dolostones. At the stratotype and in Burgueño Quarry, conglomerates overly with erosional unconformity the MVG. These conglomerates, assigned to LVFm (Blanco & Gaucher, 2004, 2005), include a level of diamictites and breccias at the contact to the MVG, which has been recognized as a palaeokarst surface. The assocation of palaeokarst surfaces developed on top of carbonate successions and overlain by glacigenic diamictites is well known for a number of Neoproterozoic successions. Dropstones occur in laminated mudstones, associated with diamictites. However, no carbonates occur on top of the diamictites. We carried out 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates. 13C and 18O analyses of carbonates and corresponding petrographic studies at two sections of the MVG and also on carbonates mined for the cement industry at La Plata Mine (ANCAP), with the aim of testing chemostratigraphic tools as an aid for the exporation of cement-grade carbonates.